Genetic diversity and phylogenetic relationship among Anabantoidei fish (Anabantiformes) in South Kalimantan, Indonesia based on SDS-PAGE analysis - Rani Sasmita; Mabrur Mabrur; UMMY SHALIHA AULIA RAHMY; Badruzsaufari Badruzsaufari (Society for Indonesian Biodiversity, 2019)
Abstract. Sasmita R, Mabrur, Rahmy USA, Badruzsaufari. 2019. Genetic diversity and phylogenetic relationship among Anabantoidei fish (Anabantiformes) in South Kalimantan, Indonesia based on SDS-PAGE analysis. Biodiversitas 20: 2519-2527. Protein profile is a molecular marker for diversity and phylogenetic analysis of germplasm, including Anabantoidei fish which is abundant in freshwater ecosystem of South Kalimantan. The aim of this research was to analyze genetic diversity and construct phylogenetic relationship among Anabantoidei fish based on SDS PAGE analysis. Protein was extracted from muscle tissue of six species of Anabantoidei fish and precipitated using Ammonium sulfate salt. Soluble protein content was determined using Bradford assay and then separated based on SDS-PAGE method. Genetic diversity and phylogenetic relationship were constructed using PAST software based on UPGMA method. The results showed that the soluble protein of fish muscle can be precipitated optimally in different ammonium sulfate concentration. Based on SDS-PAGE analysis, 59 different protein bands have been separated from gels with molecular weight ranging from 28.15 to 181.61 kDa. On the protein level, the Anabantoidei fish showed high genetic polymorphism (greater than 90%) with 3, 2 and 5 monomorphic bands on non-precipitated, AS-precipitated and combination between non- and AS-precipitated proteins, respectively. The phylogenetic reconstruction also exhibited that the Anabantoidei fish has the unique phylogenetic trees, especially for the combined protein datasets. This information would be useful for freshwater fish conservation and breeding programs.